Ressourcenpolitik und Geschlechtergerechtigkeit: Probleme lokaler und globaler Governance am Beispiel Wasser - Bauhardt, Christine (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2009)
Resource politics means the access to resources, the use of resources and the governance of resources. The current debate on climate change contributes to the ongoing social and economic injustice within gender relations. The article asks for non-hegemonic approaches to resource politics striving for gender equity and suggests a feminist understanding of sustainable livelihood as an adequate concept.